Fenomenologi Parasosial Cinta dan Pemain Deepspace Melalui Sistem Gacha - Araiya Madani Sholawati; Sidiq Setyawan (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2026)
The otome game phenomenon, Love and Deepspace, has evolved into a space for both emotional and financial investment among players. This study analyzes how players form and maintain parasocial interactions (PSI) and parasocial relationships (PSR) with game characters, which are subsequently reinforced through the gacha system. Utilizing a qualitative method with an Interpretative Phenomenological Analysis (IPA) approach, four players were interviewed. The findings reveal that immersive features and daily routines effectively cultivate emotional attraction. This intimacy is then commodified through the gacha system to unlock further romantic narratives. Furthermore, the study identifies real-world relationship status as a key differentiator: single players often utilize these interactions as a primary coping mechanism, whereas players with real-life partners maintain distinct boundaries. This study concludes that parasocial relationships in modern gaming have transitioned into transactional activities that exploit emotional needs via the gacha mechanism.